Correlation and Path Analysis for Yield and Yield Attributes in Maintainer Lines of Rice (Oryza sativa L.) - Edukondalu,; Reddy, V. Ram; Rani, T. Shobha; Kumari, Ch. Aruna; Soundharya, B. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during kharif season (June–October) of 2016 at the Regional Agricultural Research Station, Agriculture College, Professor Jayashankar Telangana State Agricultural University (PJTSAU), Jagtial, Telangana, India. Forty (40) maintainer lines of rice (Oryza sativa L.) were grown in randomized block design replicated twice to find the relationships between the yield and its components, as well as their direct and indirect effects on the rice grain yield. Observations were recorded for yield, yield attributing characters and quality traits on five randomly selected competitive plants for each entry in each replication for 15 characters. The results revealed that the analysis of variance was significant for all the characters investigated. Grain yield was significantly correlated with its component characters like number of tillers plant-1 (0.9191**), panicle length (0.3339**), milling percentage (0.3214**) and hulling percentage (0.2873**) whereas it showed a negligible positive correlation with days to 50% flowering, days to maturity, plant height, panicle length, number of grains per panicle, kernel length, kernel breadth, L/B ratio, test weight, hulling percentage, and head rice recovery percentage. Path coefficient analysis revealed that number of tillers plant-1 (0.9439) exerted maximum positive direct effect on plant yield followed by kernel breadth, L/B ratio, panicle length, milling percentage, days to flowering and head rice recovery percentage indicated their importance in determining the complex character and therefore should be kept in mind while practicing selection aimed at improving the grain yield.